STUDIES ON LOCULOASCOMYCETES : DIDYMOSPHAERIA - RAMESH, CH. (Indian Phytopathology, 2002)
The present paper deals with six species of Didymosphaeria which are described and illustrated. Of these, three are new species and the remaining are new to India. These six species are D. endoleucae, D. lonicerae, D. malloti sp. nov., D. sellae, D. shirkolaensis sp. novo and D. uaitarnensis sp. novo